An Effective Algorithm for Specular Reflection Image Enhancement - Zhuang Huang (IEEE, 2021)
Specular highlights often exist in real-world images due to the material property of objects and the capturing environments. High light in real-life scenes can reduce image quality and cause loss of image information, to overcome this, we propose an effective specular reflection image enhancement algorithm. First, the scene depth map of specular reflection image was obtained by the color attenuation prior method; then, two adaptive adjustment factors were developed to optimize the transmission map for specular reflection images and $L_{0}$ gradient minimization filter was used to eliminate halo artifacts. Finally, the nonuniform illumination compensation strategy based on the YUV color space was used to expand the dynamic range of the image and increase the saturation of the image. Experimental results via subjective and objective evaluations demonstrate that the proposed method can provide better visual quality than other methods and can effectively enhance the information in the specular reflection image.